FENOMENA BULLYING BERBASIS SENIORITAS DI LINGKUNGAN MAHASISWA UNIVERSITAS NEGERI MEDAN - Jepfri Lumban Gaol; Elchie Setia Kasih; Reggina Valentina Sipayung; Ariel Pimbro Hasugian; Aulia Hakim Dalimunthe; Lemuel Hezekia Gavriel; Parlaungan Gabriel Siahaan (STKIP Subang, 2026)
Seniority-based bullying in higher education is a serious structural problem often overlooked due to normalized hierarchical culture among student cohorts. This study aims to: (1) identify forms of seniority-based bullying; (2) analyze causal factors; and (3) describe its impact on the psychological and academic conditions of students at the Faculty of Economics and Business, Universitas Negeri Medan (FEB UNIMED), cohorts 2023–2025. A descriptive quantitative approach with purposive sampling was applied to 97 respondents across nine study programs. Instruments were tested using Cronbach's Alpha and analyzed through descriptive statistics, frequency distribution, Pearson correlation, and simple linear regression. Results show 53.6% of respondents experienced or witnessed seniority-based practices. Dominant forms include witnessing unpleasant treatment (55.7%) and coercion by seniors (47.4%), while avoidance of senior interaction reached 53.6%. Key causal factors were organizational culture supporting seniority (56.7%), juniors' fear of reporting (52.6%), and perceived senior power (51.5%). Psychological impacts were reported by 25.8% of respondents. Regression analysis shows causal factors predict bullying forms (β = 0.691, R² = 0.684, p < 0.001), and bullying forms predict psychological impact (β = 0.622, R² = 0.452, p < 0.001). These findings underscore the urgency of academic culture transformation through anonymous reporting systems, organizational intervention, and structured anti-bullying policy implementation.